Classroom interaction Patterns and Its Relation to Handball Dribbling and Passing for Sophomore Students - Hussein, yasir; Abdulazeen, Tamadur (Journal of Physical Education, 2022)
The study aimed at designing a scale for measuring classroom interaction from students’ point of view as well as measuring the pattern of classroom interaction from the students’ point of view in handball for second year college of physical education and sport sciences / University of Baghdad. The research also aimed at identifying the relationships between classroom interaction patterns and performing some handball skills in sophomore students. The researchers used the descriptive method on 110 construction subjects and applied the scale on 212 students. The results showed a strong correlation between classroom interaction pattern and final handball skill score in dribbling and passing. The researchers concluded that classroom interaction patterns have a strong correlation with one another thus each pattern can be used as an indicator for the other two patterns. Finally, the concluded that there is no relation between passing and dribbling with classroom interaction patterns.